Basaloid Carcinoma of the Breast Mimicking Cutaneous Basaloid Neoplasms. (September 2015) - Solus, Jason F.; Goyal, Amrita; Duncan, Lyn M.; Nazarian, Rosalynn M.
Abstract : Abstract: Basaloid carcinoma of the breast (BCB) is a rare, triple-negative aggressive primary breast tumor that can closely mimic cutaneous basal cell carcinoma (BCC), neuroendocrine tumors, adnexal neoplasms, and other primary breast tumors. Accurate diagnosis of this tumor is critical for appropriate clinical management. We add to the literature 2 female patients with BCB presenting with a nipple mass. Histopathologic findings from both patients showed dermal nests and cords of atypical basaloid cells with epidermal involvement, closely resembling cutaneous BCC. A panel of immunohistochemical stains, including the novel use of CK17, is essential for differentiating BCB from mimickers. BCB is a rare primary breast tumor that follows an aggressive clinical course and closely mimics many basaloid neoplasms, including cutaneous BCC clinicopathologically. Increased awareness of BCB among dermatologists and dermatopathologists is critical for accurate diagnosis and patient care.